The role of universal stress protein Usp1413 in meropenem adaptive resistance and environmental stress responses in Acinetobacter baumannii - Sirui Zhang; Jingdan Wang; Rong Yu; Haiping Liu; Shuyan Liu; Kai Luo; Jin'e Lei; Bei Han; Yanjiong Chen; Shaoshan Han; E Yang; Meng Xun; et al. (Current Research in Microbial Sciences)
Although various mechanisms of carbapenem-resistance have been identified in the nosocomial pathogen Acinetobacter baumannii, the critical process of resistance evolution and the factors involved in are not well understood. Herein, we identified a universal stress protein Usp1413 which played an important role in adaptive resistance of A. baumannii to meropenem (MEM). Based on RNA-Seq and genome sequencing, Usp1413 was not only one of the most downregulated USPs, but also the bare one having mutation of tyrosine and glycine inserted at the site of 229-230 (YG229-230) under the stimulation of MEM. Deletion of Usp1413 resulted in increased MEM resistance. In addition, Usp1413 affected the bacterial abilities of biofilm formation and swarm motility, as well as helped A. baumannii response to various environmental stresses. These effects of Usp1413 were achieved by regulating its interaction proteins, within the functions of YigZ family protein, acetyltransferase, and SulP family inorganic anion transporter. The insertion mutation of YG229-230 influenced both the expression of interaction proteins and the phenotypes of bacteria. Finally, the promotor region of Usp1413 was convinced by point mutations. Overall, our findings identified the universal stress protein Usp1413 as a contributor involved in MEM adaptive resistance and responded to numerous environmental stresses. This study provides novel insights into the mechanism of universal stress proteins in participating antibiotic resistance, and affords a potential target for controlling drug resistance development in A. baumannii.